Temporary Thyroid Dysfunction and Catecholamine Excess Due to Mercury Poisoning in 6 Cases - Yavuz Özer; Mehmet Yıldız; Hande Turan; Aydilek Dağdeviren Çakır; Gürkan Tarçın; Dilek Bingöl Aydın; Elvan Bayramoğlu; Fatih Haşlak; Sezgin Şahin; Amra Adrovic; Kenan Barut; Olcay Evliyaoğlu; et al. (AVES Yayincilik, 2024)
Objective: Mercury poisoning is a condition with multiple-organ dysfunction that has effects on the central nervous system, gastrointestinal system, cardiovascular system, skin, lungs, and kidneys. It can be fatal or may result in sequelae such as neurological disturbances, if treated late or left untreated. The endocrinological effects of mercury exposure are not well-known. We aimed to evaluate patients with mercury poisoning. Materials and Methods: A total of 6 cases of mercury poisoning from 3 families were included in the study. Clinical, laboratory, and follow-up data were recorded. Results: Thyroid dysfunction was presented as high thyroid hormones and normal thyrotropin level (unsuppressed) in 5 cases (83.3%). On the other hand, pheochromocytoma-like syndrome was detected in 5 cases (83.3%) with hypertension. The 4 cases were the first to use methimazole for mercury poisoning due to tachycardia and hypertension despite antihypertensive treatment due to catecholamine excess and thyroid dysfunction. Hyponatremia was detected in 3 cases (50%). Conclusion: Mercury poisoning is difficult to diagnose because it is rare and presents with nonspecific physical and laboratory findings. Early diagnosis and providing appropriate treatment are essential in order to prevent sequelae. Mercury poisoning should be considered in patients with unexplained hypertension and tachycardia suggesting the involvement of thyroid hormones and catecholamines